Peran Angka Partisipasi Murni dan Angka Harapan Lama Sekolah terhadap Jumlah Publikasi sebagai Wujud Literasi Bahasa Indonesia: Penelitian - Titian Dhea Fresensia Purba; Sri Rosni Alfiat Laia; Flowrensari Haggata Br Ginting; Reymon Pernando Pasaribu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the influence of the Net Enrollment Rate (NER) and the Expected Years of Schooling (AHLS) on the number of publications as a form of Indonesian language literacy. The research method uses a quantitative approach with multiple regression analysis based on annual secondary data for the 2010–2023 period obtained from the Central Statistics Agency (BPS). Classical assumption tests were conducted to ensure that the regression model meets the BLUE criteria. The results show that the NER has a positive and significant effect on the number of publications, while the AHLS does not have a significant partial effect. However, simultaneously, the NER and AHLS have a significant effect on the number of publications, with an R-Square value of 64.57%. This indicates that educational participation not only influences the level of community involvement in the formal education system but also determines the extent to which the younger generation is able to produce high-quality academic work. In other words, equitable and sustainable education plays a crucial role in creating a productive literacy ecosystem, particularly in the realm of Indonesian as the national language and language of science. These findings confirm that educational participation has a crucial role in improving academic literacy and productivity in Indonesia.